Operational frequency degradation induced trapping in scaled GaN HEMTs - Karol Kalna (Microelectronics Reliability, 2017)
Cut-off frequency increase from 12.1 GHz to 26.4 GHz, 52.1 GHz and 91.4 GHz is observed when the 1 μm gate length GaN HEMT is laterally scaled down to LG = 0.5 μm, LG = 0.25 μm and LG = 0.125 μm, respectively. The study is based on accurately calibrated transfer characteristics (ID-VGS) of the 1 μm gate length device using Silvaco TCAD. If the scaling is also performed horizontally, proportionally to the lateral (full scaling), the maximum drain current is reduced by 38.2% when the gate-to-channel separation scales from 33 nm to 8.25 nm. Degradation of the RF performance of a GaN HEMT due to the electric field induced acceptor traps experienced under a high electrical stress is found to be about 8% for 1 μm gate length device. The degradation of scaled HEMTs reduces to 3.5% and 7.3% for the 0.25 μm and 0.125 gate length devices, respectively. The traps at energy level of ET = EV + 0.9 eV (carbon) with concentrations of NIT = 5 × 1016cm− 3, NIT = 5 × 1017cm− 3 and NIT = 5 × 1018cm− 3 are located in the drain access region where highest electrical field is expected. The effect of traps on the cut-off frequency is reduced for devices with shorter gate lengths down to 0.125 μm.